Technological acceptance of e-commerce by generation Z in Portugal - Duarte, C.; Messias, I.; Oliveira, A. (Information, 2024)
E-commerce allows consumers to make online purchases easier, faster and at any time, making it different from traditional commerce. This technology has grown recently and has become popular among younger generations. This is the case of Generation Z, a technological generation that will become the leading group of consumers in the coming years. Despite the positive results regarding this practice, the expected results for the Western world, a world of which Portugal is a part, have yet to be achieved. The main objective of this investigation was to understand the acceptance of e-commerce by Generation Z in Portugal. The nature of this study is quantitative and used the questionnaire for data collection based on the proposed conceptual model built through the literature review. The dimensions obtained were analysed using the SmartPLS 4 and IBM SPSS Statistics 26 tools. The results allowed responding to the proposed objectives to support or reject the defined hypotheses associated with the variables trust, perceived risk, perceived ease of use, attitude, perceived usefulness, intention to use, privacy and security. It was also possible to define the digital consumer profile of Generation Z in Portugal.